The Use of System Usability Scale as an Evaluation of Shopee PayLater - Hasudungan, Jonlisen; Arifianto, Firman; Achsan, Harry T. Y. (STKIP PGRI Tulungagung, 2024)
The increasing popularity of e-commerce in Indonesia has led to the emergence of a variety of financial services that support online transactions, such as Pay Later. Pay Later is a feature that allows users to make purchases on credit, with the option to pay later in installments. One of the most popular e-commerce platforms in Indonesia is Shopee. Shopee offers a Pay Later feature that allows users to make purchases on credit. However, the concept of Pay Later has not yet been fully accepted by the public. Some of its functions are still confusing for ordinary users. A study conducted by the University of Indonesia investigated the usability of the Shopee Pay Later feature. The study used the System Usability Scale (SUS) to measure the usability of the feature. The SUS is a 10-item questionnaire that is used to assess the usability of a system. The results of the study showed that the System Usability Scale score for the Shopee Pay Later feature was 75.38. This score indicates that the feature has an overall usability rating of